An improved total station measurement method for the georeferenced orientation of self-propelled artillery barrel. (July 2022) - Cheng, Zejun; Wang, Huaiguang; Han, Lanyi; Du, Binhan; Shi, Zhiyong
Highlights: Proposed a method for measuring the barrel orientation of self-propelled artillery combining total station, RNSS positioning and orientation instrument and magnetic target. Introduced north datum for self-propelled artillery barrel orientation. Solved the problem of axis simulation errors during the measurement process. Analyzed the influence of total station layout scheme on measurement accuracy and suppressed it based on the Monte Carlo method. Developed the corresponding automatic calculation program of gun barrel positioning. Abstract: Self-propelled artillery is the main suppressing weapon installed by the armies of various countries, which plays an important role in modern warfare. With the continuous development of military science and technology, modern warfare has put forward higher requirements for the autonomous combat capability and precision strike capability of self-propelled artillery. Therefore, it is necessary to measure and verify the orientation of the self-propelled artillery barrel after maintenance and before firing. Among the various methods to achieve high-precision measurement of self-propelled artillery barrel orientation, the total station measurement method has shown good results in measurement accuracy, cost-effectiveness, and applicability to complex environments. However, there are some problems in the traditional total station measuring barrel orientation method, such as the lack of a north benchmark and the barrel calibration error. Therefore, this study aimed to develop an improved method for measuring the barrel orientation of self-propelled artillery, which solved the above problems by integrating the standard north orientation and the simulated axis of the barrel using a total station. First, to establish the measurement coordinate system of the measurement area, the standard north orientation of the measurement field area is determined using a positioning orientation instrument based on the Radio Navigation Satellite System. Second, to complete the barrel calibration, two magnetic target plates are set on the barrel, and a fixed spatial positional relationship between the connection line of the magnetic target center points and the barrel axis is established. Third, the barrel of self-propelled artillery is adjusted to the measurement attitude, and the magnetic target is observed and sighted with a total station to obtain its spatial coordinates in the measurement coordinate system. Subsequently, the error analysis of the measurement plan was carried out, and it was found that the position of the total station had a great influence on the measurement accuracy of the barrel orientation. Therefore, the uncertainty model of the measurement accuracy about the location of the station is established, and the station deployment area is scanned based on the idea of the Monte Carlo method to find the optimal measurement area. Finally, a certain type of self-propelled artillery is used to carry out an installation experiment. The experiment shows that the improved method solves the problems of the traditional method which lacks a north benchmark and the barrel calibration error, and can ensure that the measurement error is within 0.2mil, which assists in the development of precision self-propelled artillery strikes.